Safety and immunogenicity of the live attenuated intranasal pertussis vaccine BPZE1: a phase 1b, double-blind, randomised, placebo-controlled dose-escalation study. Issue 11 (November 2020) - Jahnmatz, Maja; Richert, Laura; al-Tawil, Nabil; Storsaeter, Jann; Colin, Céline; Bauduin, Claire; Thalen, Marcel; Solovay, Ken; Rubin, Keith; Mielcarek, Nathalie; Thorstensson, Rigmor; Locht, Camille; et al.
Summary: Background: Long-term protection and herd immunity induced by existing pertussis vaccines are imperfect, and a need therefore exists to develop new pertussis vaccines. This study aimed to investigate the safety, colonisation, and immunogenicity of the new, live attenuated pertussis vaccine, BPZE1, when given intranasally. Methods: This phase 1b, double-blind, randomised, placebo-controlled, dose-escalation study was done at the phase 1 unit, Karolinska Trial Alliance, Karolinska University Hospital, Stockholm, Sweden. Healthy adults (18–32 years) were screened and included sequentially into three groups of increasing BPZE1 dose strength (10 7 colony-forming units [CFU], 10 8 CFU, and 10 9 CFU), and were randomly assigned (3:1 within each group) to receive vaccine or placebo. Vaccine and placebo were administered in phosphate-buffered saline contained 5% saccharose as 0·4 mL in each nostril. The primary outcome was solicited and unsolicited adverse events between day 0 and day 28. The analysis included all randomised participants who received a vaccine dose. Colonisation with BPZE1 was determined by repeatedly culturing nasopharyngeal aspirates at day 4, day 7, day 11, day 14, day 21, and day 28 after vaccination. Immunogenicity, as serum IgG and IgA responses were assessed at day 0, day 7, day 14, day 21, day 28, 6 months, and 12 months after vaccination. This trial is registered at Clinicaltrials.gov, NCT02453048 . Findings: Between Sept 1, 2015, and Feb 3, 2016, 120 participants were assessed for eligibility, 48 of whom were enrolled and randomly assigned (3:1) to receive vaccine or placebo, with 12 participants each in a low-dose, medium-dose, and high-dose vaccine group. Adverse events between day 0 and day 28 were reported by one (8%, 95% CI 0–39) of 12 participants in both the placebo and low-dose groups, and two (17%; 2–48) of 12 participants in both the medium-dose and high-dose groups, including cough of grade 2 or more, oropharyngeal pain, and rhinorrhoea and nasal congestion. During this time, none of the participants experienced any spasmodic cough, difficulties in breathing, or adverse events following immunisation concerning vital signs. The tested doses of BPZE1 or placebo were well tolerated, with no apparent difference in solicited or unsolicited adverse events following immunisation between groups. Colonisation at least once after vaccination was observed in 29 (81%; 68–93) of 36 vaccinated participants. The tested vaccine doses were immunogenic, with increases in serum IgG and IgA titres against the four B pertussis antigens from baseline to 12 months. Interpretation: The tested vaccine was safe, induced a high colonisation rate in an adult population, and was immunogenic at all doses. These findings justify further clinical development of BPZE1 to ultimately be used as a priming vaccine for neonates or a booster vaccine for adolescents and adults, or both. Funding: ILiAD Biotechnologies.